(untitled) (GYMNASIUM, 2017)
This study aims to present a personal point of view on the adventure tourism activities that lately recorded an increase in popularity, mostly among children and adolescents. We are talking about climbing on artificial structures, via ferrata, Tyrolean traverse, tree climbing, activities united under the name "Adventure Park," but also about fast water sports, called "whitewater sports," to which we add canyoning, at the border of the above mentioned sports. This touristic athletic activities that are performed in nature have appeared and developed. They attract more and more people through the adventure, action, and thrills they offer. Although they are addressed to a large segment of the population, they are more attractive to the younger generation, who want to test and develop their skills. Adventure tourism gives another dimension to self-knowledge, being the exponent of courage, motor intelligence, of certain predominantly physical qualities.